Impulse Control Disorders and Dopamine-Related Creativity: Pathogenesis and Mechanism, Short Review, and Hypothesis - Garcia-Ruiz, Pedro J. (Frontiers in Neurology, 2018)
Impulse control disorder (ICD), including pathological gambling, hypersexuality, and compulsive shopping has been linked to antiparkinsonian medication, especially dopamine agonists. The mechanism of ICD is not completely clear, but it seems that ICD is the result of an activation of dopamine receptors, mostly D3 in the ventral striatum. Patients treated with dopamine agonists that have preferential affinity for D3 (including ropinirole and pramipexole) are much more prone to develop ICD. In addition, a genetic component is probably present, especially in young patients. Finally, environment and lifestyle may also play a role: those patients engaged in physical, social, and artistic activities are probably less likely to develop ICD compared to those patients with poor physical activity living in isolated environments.